2004
DOI: 10.3748/wjg.v10.i9.1240
|View full text |Cite
|
Sign up to set email alerts
|

GSTT1,GSTM1andCYP2E1genetic polymorphisms in gastric cancer and chronic gastritis in a Brazilian population

Abstract: AIM:To test the hypothesis that, in the Southeastern Brazilian population, the GSTT1, GSTM1 and CYP2E1 polymorphisms and putative risk factors are associated with an increased risk for gastric cancer. METHODS:We conducted a study on 100 cases of gastric cancer (GC), 100 cases of chronic gastritis (CG), and 150 controls (C). Deletion of the GSTT1 and GSTM1 genes was assessed by multiplex PCR. CYP2E1/PstI genotyping was performed using a PCR-RFLP assay. RESULTS:No relationship between GSTT1/GSTM1 deletion and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 53 publications
2
22
0
1
Order By: Relevance
“…GSTM1, GSTT1 and GSTP1 genes of the GST super gene family exhibit polymorphisms, which are associated with reduced enzyme activity (Pemble et al, 1994;Hayes et al, 1995;Ali-Osman et al, 1997). The results on the association of GST polymorphisms with gastric cancer are contradictory by previous studies (Colombo et al, 2004;Tamer et al, 2005You et al, 2005Martinez et a;. The difference might be due to ethnic variations, or differences in expression of GST genes.…”
Section: Introductionmentioning
confidence: 88%
“…GSTM1, GSTT1 and GSTP1 genes of the GST super gene family exhibit polymorphisms, which are associated with reduced enzyme activity (Pemble et al, 1994;Hayes et al, 1995;Ali-Osman et al, 1997). The results on the association of GST polymorphisms with gastric cancer are contradictory by previous studies (Colombo et al, 2004;Tamer et al, 2005You et al, 2005Martinez et a;. The difference might be due to ethnic variations, or differences in expression of GST genes.…”
Section: Introductionmentioning
confidence: 88%
“…Deletion of GSTT1 was found not to be associated with gastric cancer risk in several studies in a variety of populations (17,(20)(21)(22)(23)(24)(25)(26)(27). One study in Poland found a significant increase in risk for null GSTT1 limited to cases with age <50 years (28); another study in China reported a significant OR of 2.5 for GSTT1 deletion (29).…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous deletions of these genes, referred to as GSTM1 null and GSTT1 null, respectively, result in lack of enzyme activity. Null mutations of these genes have been associated with increased risk for a number of cancers in some studies (6-11), but not in others (12)(13)(14)(15)(16). Two studies have reported modest associations between nasopharyngeal carcinoma and GSTM1 and/or GSTT1 deletions; however, these studies were quite small, with less than 100 nasopharyngeal carcinoma cases (17,18).…”
Section: Introductionmentioning
confidence: 96%